IMPLEMENTASI METODE PRESENTASI EKSTEMPORE UNTUK MENINGKATKAN KREATIVITAS SISWA PADA MATA PELAJARAN FIQIH DI SMPIT LUQMANUL HAKIM - Zuliana, Zuliana; Fadillah, Anisa; Qorib, Muhammad (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2024)
This research aims to determine the implementation of the extempore presentation method in increasing student creativity in the Fiqh subject at SMP IT Luqmanul Hakim. This research was based on the problem of choosing monotonous learning methods, so that this extempore presentation method can be a fun learning alternative. This research method uses a qualitative research method with a descriptive qualitative research type. Data collection techniques include direct observation at the research location, interviews with school principals and teachers, and research documentation. The data analysis technique used is the Miles and Huberman Model. Then this research uses data validity in the form of trustworthiness, transferability and confirmability. Based on the results of research and data analysis, it can be concluded that the extempore presentation method is a learning method that is quite effective in increasing student activity in the classroom, developing student creativity, training self-confidence, and improving language style in conveying information